Three perspectives on sustainable food security: efficiency, demand restraint, food system transformation. What role for life cycle assessment? - Garnett, Tara (Elsevier, 2014)
Achieving food system sustainability is a global priority but there are different views on how it might be achieved. Broadly three perspectives are emerging, defined here as: efficiency oriented, demand restraint and food system transformation. These reflect different conceptualisations on what is practically achievable, and what is desirable, underpinned by different values and ideologies about the role of technology, our relationship with nature and fundamentally what is meant by a ‘good life.’ This paper describes these emerging perspectives and explores their underlying values; highlights LCA's role in shaping these perspectives; and considers how LCA could be oriented to clarify thinking and advance policy-relevant knowledge. It argues that more work is needed to understand the values underlying different approaches to the food sustainability problem. This can shed light on why stakeholders disagree, where there are genuine misunderstandings, and where common ground is possible and ways forward agreed.